2020
DOI: 10.5502/ijw.v10i3.1321
|View full text |Cite
|
Sign up to set email alerts
|

Job security and the promotion of workers’ wellbeing in the midst of the COVID-19 pandemic: A study with Canadian workers one to two weeks after the initiation of social distancing measures

Abstract: Background: Due to the current coronavirus (COVID-19) crisis, workplaces have had to make significant alterations in the way they conduct business. This, in addition to the current financial instability, may put workers at risk of experiencing job insecurity and, in turn, lower wellbeing. Job insecurity is a key determinant of wellbeing, but little is known on how it is impacted by public health crises, and more specifically how it relates to workers' positive and negative wellbeing in the midst of a pandemic.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
71
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 32 publications
8
71
2
1
Order By: Relevance
“…Moreover, job security was also associated with a reduced level of distress. Similar results were reported only 2 weeks after the measures were introduced (Pacheco et al, 2020).…”
Section: Job Insecurity As a Predictor Of Distresssupporting
confidence: 86%
“…Moreover, job security was also associated with a reduced level of distress. Similar results were reported only 2 weeks after the measures were introduced (Pacheco et al, 2020).…”
Section: Job Insecurity As a Predictor Of Distresssupporting
confidence: 86%
“…Given the unique health and economic context of the pandemic, including potential labour shortages coupled with the need to ensure adequate protection for workers [ 56 , 57 , 58 ], future research should examine outcomes beyond initial infection risk, as well as the key barriers, enablers and mitigation strategies that drive differences in these outcomes [ 59 ]. Future research should also examine these factors in relation to other occupation and industry groups that are underrepresented in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that workplace interventions need to be targeted towards modifiable risk factors at the individual and organizational level [ 59 , 64 ]. For example, recent studies have found that job security [ 56 ] and perceived adequacy of PPE and workplace-based infection control procedures [ 57 ] may be important variables that influence the risk of worse mental health symptoms. Future research should continue to explore how these factors and others identified in the included reviews can be targeted to address mental health and well-being concerns as workplaces re-open or continue to re-open [ 59 ], as well as evaluation studies that examine their effectiveness over time.…”
Section: Discussionmentioning
confidence: 99%
“…Almost every participant expressed that they either lost their jobs or feared losing one (Moen et al, 2020;Pacheco et al, 2020). Economic activities and business worldwide came to a halt during the lockdown.…”
Section: Life In Covid-19: Lost Employment or Fear Of Losing Itmentioning
confidence: 99%